(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
Through a qualitative and quantitative analysis of data on GVC membership and Malaysia’s GDP from 2000 to 2022, this paper talked about what GVC is, how important it is to be a part of it, and how it affects economic growth. The premise that underpins the study is that GVC membership contributes positively to economic development. Does GVC membership affect Malaysia’s economic development throughout the study period? The industrial sector contributes significantly to both local and foreign added value in exports, and participation in GVC has a positive impact on economic growth in Malaysia during the studied period. The impact is reciprocal between GVC participation and the industrial sector. Additionally, connecting the local market to the foreign market helps to provide advanced intermediate inputs and introduce modern production methods and technology that increase the competitive and productive capabilities of local companies. GVC also gets more companies involved through forward and backward links because it lets them specialize in a part of the production process instead of finishing the whole thing. This makes it easier for new companies to get into the market and makes them more competitive.